The Effect of Liquidity, Leverage and Profitability on Financial Distress - Volta Diyanto (Indonesian Journal of Economics, Social, and Humanities, 2020)
This study aims to analyze the effect of liquidity, leverage, and profitability on financial distress in manufacturing companies in Riau province. 129 manufacturing companies experiencing financial distress in Riau province were selected as samples using purposive sampling method. The data were analyzed using multiple linear regression. The results show that the current ratio affects financial distress. The debt to equity ratio affects financial distress. Return on assets affects financial distress.